Pica sebagai Manifestasi Anemia Defisiensi Besi: Suatu Laporan Kasus - murwaningrum, artati; Rinaldi, Ikhwan; Mustopa, Inna Intani (Jurnal Penyakit Dalam Indonesia, 2023)
Prevalence of anemia in Indonesia based on Basic Health Research (2018) was 23.7%. Symptoms of iron deficiency anemia were pallor, malaise, palpitation, shortness of breath, headache, sore tongue. But sometimes can be found abnormal behavior in the form of PICA. This article reports on a-52-year-old man who sought medical treatment and was diagnosed with iron deficiency anemia with pica manifestation. The pica manifestation was characterized by a repeated desire to consume raw rice due to bleeding from hemorrhoids. Patient was given oral iron replacement therapy contain 100 mg of Fe (III) hydroxide polymaltose complex and folic acid 0.35 mg alternating with vitamin C 500 mg daily. Total iron daily dose given were 200 mg, divided in two doses. The patient received dietary education and was advised to consult a Gastroenterohepatology Subspecialist for the management of hemorrhoids, but it has not been done yet. The desire for raw rice consumption disappeared and the hemoglobin level increased to 12.4 g/dL after six weeks of therapy. The patient continued to take iron supplements until January 2023 but did not have follow-up visits to the clinic. In January 2023, the patient underwent hemorrhoid surgery due to bleeding accompanied by and a non-reducible lump that had been present for three days. Iron supplements continued for one month post-operation and then discontinued. The latest hemoglobin level was 15.3 g/dL without iron supplements. The symptoms of pica in this patient disappeared along with an increased hemoglobin level, and the management of severe anemia in this patient showed an adequate response. Bleeding has never occurred again after the surgery. Curative measures for hemorrhoidal bleeding are crucial, while iron supplementation is only a supportive therapy.